Concomitant Colonization of Helicobacter pylori in Dental Plaque and Gastric Biopsy. (9th July 2014) - Abadi, Amin Talebi Bezmin; Mobarez, Ashraf Mohabati; Teymournejad, Omid; Karbalaei, Mona
Abstract : Frequently reported H. pylori antimicrobial therapy failures suggest that there might be a different niche where the bacteria can stay safe. Current study aims to examine potential role of oral colonization of H. pylori to feed reinfection after primary therapy. However, patients who were admitted to the gastroscopy section were chosen and gastric biopsy and dental plaque specimens were collected. Molecular and biochemical tests were applied to confirm H. pylori identity in different colonization niches. Results showed that 88.8% of dyspeptic patients had epigastric pains with nocturnal awakening when they were hungry (P = 0.023 ). All patients who received therapy already were again H. pylori positive while they are still carrying H. pylori in dental plaque (P = 0.001 ). Moreover, H. pylori infection was sought in 100% of gastric biopsy's dyspeptic patients who had ulcerated esophagitis and erosive duodenitis and who were H. pylori positive, and 75% of dyspeptic patients with duodenum deformity had this bacterium in gastric biopsies (P = 0.004 ). Present study showed that only successful eradication of gastric H. pylori cannot guarantee prevention of reinfection. Conclusively, a new strategy which indicates concomitant eradication in oral and gastric colonization can result in clearance of H. pylori infection.